Peran Harapan sebagai Mediator Antara Partisipasi dalam Mengambil Keputusan dan Kepuasan Kerja pada Karyawan - Alissa, Shavira; Martina Dwi, Mustika (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2024)
Covid-19 caused economic deflation in Indonesia because of the limitation of physical interaction between humans, so that the organization could not operate optimally. In this case, companies in Indonesia have to prepare strategies aimed at restoring the economy, one of which is by maximizing the potential of employees in achieving organizational goals. Employees in a company have a crucial role, so it is necessary to optimize employees to achieve organizational success. Maintaining job satisfaction is the best way to optimize potential employees. Employee job satisfaction is predicted by the participation in decision making, including with the hope. This study aims to determine the role of mediation between variables. The participants amounted to 447 represented by approximately 100 employees from four industrial sectors (modern retail, automotive, life insurance, and property). The study was conducted with a quantitative approach using the Employee PDM, Hope, and Job Satisfaction measurements. The results show that participation in decision making to job satisfaction mediated by hope through mediation tests (p <0.005). To increase job satisfaction, employees need to increase their involvement in organizational decision making which also increases their expectations. This study proves that the level of participation can have a positive impact on the organization, which has an impact on job satisfaction in the form of more effective performance. In addition, this also affects the employee's encouragement to complete his work. Furthermore, hope can have a significant indirect effect in the relationship between participation in making decisions and job satisfaction.